Connecting diversity and youth community service project: a semiotic analysis on typology of images used in social media reporting - Shahrin, Muhamad; Arshad, Mohd Mursyid; Mason, Cordelia; Abd Menon, Ami Suhana; Rashid, Rashdan (Human Resources Management Academic Research Society (HRMARS), 2024)
Social media semiotic research is an emerging powerful methodology for research and for developing brand communications. This study takes a deep dive into cultural connotations and category codes that ameliorate understanding and reinvigorate communication in society. In this study, we develop an understanding of strategic corporate and public affairs communication about community service projects that have emerged as strategic efforts to interact with society. The significance of social media reporting has been driven by the need to increase Malaysian Drug Prevention Association (PEMADAM Kebangsaan) transparency and accountability concerning social and youth issues. PEMADAM Kebangsaan develops and improves internal culture and social media communication and deploys semiotic metaphors and digital storytelling to create fresh emotional messages for younger generations. Utilizing qualitative research methodology for social media content analysis and semiotic interpretation, this study analyzes the typology of images used in its social media reporting. The change in brand communication creates disruptive innovation by starting public discourses on the role of PEMADAM Kebangsaan in society especially to stay relevant with the younger generations.